The origins of mutational robustness. Issue 7 (July 2015) - Fares, Mario A.
Highlights I examine the origins of resistance of organisms to mutations. Robustness to mutations is a universal property of biological systems. Experimental evolution of microbes reveals the origin of robustness. Genetic redundancy through gene duplication gives rise to mutational robustness.